ETIKA PEMERINTAHAN: MENJAGA INTEGRITAS DAN AKUNTABILITAS DALAM TATA KELOLA PEMERINTAHAN - Irvan Dhani Prabowo; Istiana Hermawati (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Government ethics is an important issue in good governance. This research aims to analyze the importance of government ethics in maintaining the integrity and accountability of public officials. The research method used is a literature study by collecting secondary data from various trusted sources. The research results show that government ethics includes principles such as professionalism, transparency, responsibility and justice. Implementing good government ethics can increase public trust in the government and encourage the creation of a clean, effective and efficient government. In conclusion, government ethics is an important foundation for good governance and must continue to be strengthened.